Foreign Direct Investment, Public Sector Venality and Entrepreneurship Development in Developing Countries - Dzomonda, Obey; Ngwakwe, Collins C. (International Journal of Economics and Financial Issues, 2022)
This paper evaluates the relationship between foreign direct investment (FDI) and entrepreneurship development in developing countries. The paper also analyses the intervening effect of public sector venality and the foreign direct investment effect on developing entrepreneurship in developing countries. The paper applied a quantitative research method. Secondary data collection covered four years (2016-2019). Data related to FDI were collected from the World Bank database; data for public sector corruption were collected from the Transparency International Corruption Index, and data related to entrepreneurship development were collected from the Global Entrepreneurship Monitor (GEM) reports. The sample consisted of nine developing countries which resulted in 36 observations. Data were analysed with the application of fixed effect regression. The results showed that foreign direct investment significantly affects entrepreneurship development in developing countries and that public sector venality negatively affects entrepreneurship development. The practical significance of these findings includes the need for developing countries to place pragmatic emphasis on the continuous attraction of foreign direct investment to accelerate the positive spill-over effect of foreign direct investment on local entrepreneurs, which comes with skills and technology advantages – amongst others. There is a dire need for governments in developing countries to rethink their approach toward eradicating public sector venality, which this research has confirmed as inimical to the nurturing and development of local entrepreneurship. This paper recommends an agenda for further research to explore the current model by including more samples and more time series in future analysis models.